If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(2x + -4) = 2(4x + -6) Reorder the terms: 6(-4 + 2x) = 2(4x + -6) (-4 * 6 + 2x * 6) = 2(4x + -6) (-24 + 12x) = 2(4x + -6) Reorder the terms: -24 + 12x = 2(-6 + 4x) -24 + 12x = (-6 * 2 + 4x * 2) -24 + 12x = (-12 + 8x) Solving -24 + 12x = -12 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -24 + 12x + -8x = -12 + 8x + -8x Combine like terms: 12x + -8x = 4x -24 + 4x = -12 + 8x + -8x Combine like terms: 8x + -8x = 0 -24 + 4x = -12 + 0 -24 + 4x = -12 Add '24' to each side of the equation. -24 + 24 + 4x = -12 + 24 Combine like terms: -24 + 24 = 0 0 + 4x = -12 + 24 4x = -12 + 24 Combine like terms: -12 + 24 = 12 4x = 12 Divide each side by '4'. x = 3 Simplifying x = 3
| 3x=6x-7 | | x-12=5x | | 2a-3a+4a=5a-18 | | w/2-34/5=53 | | 9x^3+12x^2-45x= | | (2x-1)(2x-1)+5=4x(x-2)-2(2x+1) | | 4x^2-500x=0 | | 65=(3-2w)(w) | | 5g-4(-5-3g)=1-1g | | w/2-34=53 | | 2w^2-3w+65=0 | | m=(12-3)/(11+1) | | 9x-1=3+8x | | 275=10(x-50)+75 | | 65=3w-2w^2 | | 3x+7=4x+8 | | 4(3m-10)-6(7m-6)=74 | | f=10(275-50)+75 | | 16=x+15 | | 5+5v=4+5v | | =5m(3m^3-4m)(7m^3-2m^2+5m+1) | | -1(2x-2y)=-1(-4) | | n+19=38 | | -2x+28+6x=42 | | f(2)=8x+3 | | 7+4x=34+4 | | 4+3y=-11 | | 7x+18=25 | | -2(-x-y)=-1(-14) | | 7x+12y=-16 | | 9u-47=2u-4 | | x-3(x+1)=6y-5x |